Crafting sustainability in iconic skyscrapers: a system of building professions in transition? - Kathryn B. Janda (Nordic Journal of Science and Technology Studies, 2017)
This paper focuses on coordination, fragmentation, and the potential for transition in the system of building professions in the American construction industry. The paper relies mainly on local press coverage of three iconic New York skyscrapers—the Empire State Building (completed in 1931), the U.N. Secretariat (completed in 1952) and One World Trade Center (completed in 2014)— to compare how the roles of different building professionals are seen by and portrayed to the public eye over time. The historic cases show how different professional groups—builders in the 1930s, architects in the 1950s, and engineers in the 2010s—imbued each project with “sustainable” qualities appropriate for its time. Using a system of professions (Abbott 1988[r]) approach, the paper describes and discusses the implications of changes in societal interest from doing to designing in American skyscrapers. The paper concludes by arguing that greater coordination between doers and designers in the construction industry, of the kind exhibited in the early days of skyscrapers, would enable the social production of sustainable buildings. For this to happen, however, society would need to place a higher value on tangible outcomes compared to lofty goals..